Structure and feeding of a stream fish assemblage in southeastern Brazil: evidence of low seasonal influences - da Rocha, F.C.; Casatti, L.; Pereira, D.C. (My University, 2009)
Aim: The present study was developed in a deforested stream located in a region that exhibits marked seasonality with the purpose to investigate whether ecological descriptors of the quantitative structure (i.e., composition, abundance, biomass, species richness, diversity) and feeding of fishes do change between the dry and wet periods. Methods: Sampling was conducted bimonthly from April 2004 to February 2005 by using a standardized effort with electrofishing equipment and environmental variables measurements. Results: We collected 713 fishes belonging to 23 species. The most abundant species were Gymnotus carapo (24.0%) and Poecilia reticulata (23.8%). Species richness, abundance, and biomass showed to be higher in the wet period, but these differences were not significant and did not influence the multivariate pattern of the assemblage (ANOSIM, R = 0.148). Nevertheless, average dissimilarity between community structure in the dry and wet periods was 52.7%, mainly due to the differential contribution of P. reticulata, notably more abundant in the wet season, under quasi-hypoxic water conditions. Examination of 333 gastric contents of 12 species evidenced that food variety was higher in the dry period. of these species, 67% (Astyanax altiparanae, Astyanax fasciatus, Geophagus brasiliensis, Gymnotus carapo, Hypostomus ancistroides, Phalloceros harpagos, Poecilia reticulata, and Rhamdia quelen) kept the diet throughout the year, being classified in the same trophic groups in both periods, and detritus was the most important item for half of them, followed by aquatic insects. Overall, no significant differences in the community's diet between periods were registered (ANOSIM, R = [long dash]0.04). Conclusions: This relative constancy suggests a quite regular availability of resources (mainly shelters in submerged marginal grasses and detritus) along the year.
Estrutura e alimentação de uma comunidade de peixes em um riacho no sudeste do Brasil: evidências de baixa influência sazonal